1998
DOI: 10.1111/j.1095-8649.1998.tb02013.x
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal cycles of gonadal development and plasma sex steroid levels in Epinephelus morio, a protogynous grouper in the eastern Gulf of Mexico

Abstract: In a field population of the protogynous red grouper Epinephelus morio in the eastern Gulf of Mexico, females with oocytes at all stages of development were collected during the spawning season suggesting that several batches of oocytes may be released over the spawning period. Plasma oestradiol (E 2 ) levels were highest in ripe females whose gonads contained both cortical alveoli and vitellogenic oocytes during the breeding season. Males were still spermiating as late as August, although levels of androgens … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
42
1
2

Year Published

2001
2001
2017
2017

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 31 publications
(52 citation statements)
references
References 24 publications
7
42
1
2
Order By: Relevance
“…Previous studies have focused mainly on the descriptions of gonad ultrastructure and histology at different developmental stages (Smith 1965;Moe 1969;Tan and Tan 1974;Bruslé and Bruslé 1975;Kuo et al 1988;Bruslé-Sicard et al 1992;Johnson et al 1998;Marino et al 2001;Bhandari et al 2003). Marino et al (2001) have depicted gonad morphology of the dusky grouper (E. marginatus) by the histological observation of 405 individuals from the Pelagie Islands in the Mediterranean Sea.…”
Section: Gonad Development and Histological Characterization In Groupersmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies have focused mainly on the descriptions of gonad ultrastructure and histology at different developmental stages (Smith 1965;Moe 1969;Tan and Tan 1974;Bruslé and Bruslé 1975;Kuo et al 1988;Bruslé-Sicard et al 1992;Johnson et al 1998;Marino et al 2001;Bhandari et al 2003). Marino et al (2001) have depicted gonad morphology of the dusky grouper (E. marginatus) by the histological observation of 405 individuals from the Pelagie Islands in the Mediterranean Sea.…”
Section: Gonad Development and Histological Characterization In Groupersmentioning
confidence: 99%
“…In males, 11-KT, teleost-specific androgen, is considered a principal androgen in teleostean fish, and it plays a central role in sexual maturation, development of secondary sexual characteristics and reproductive behaviour (Miura et al 1991;Borg 1994). In many sexchanging fish, the levels of circulating 11-KT have been reported to increase with the progression of sex change (Nakamura et al 1989;Johnson et al 1998;Kroon and Liley 2000;Bhandari et al 2003), and exogenous 11-KT treatment can induce sex reversal (Kroon and Liley 2000;Yeh et al 2003). It was found that the androgen-producing sites exist in the ovary of honeycomb grouper (Alam et al 2005) and that naturally occurring sex change is accompanied by significant increases in the size of androgen-producing cells and production of androgen by the gonads .…”
Section: Endocrine Changes and Regulation During Sex Change Of Groupersmentioning
confidence: 99%
“…In many sex-changing fish, the levels of circulating 11KT have been reported to increase with the progression of sex change (Nakamura et al ., 1989;Johnson et al , 1998;Kroon and Liley, 2000;Bhandari et al , 2003;Perry and Grober, 2003), and exogenous 11KT treatments have been shown to induce female-to-male sex change (Kroon and Liley, 2000;Yeh et al , 2003). Our previous studies suggest that a drop in E2 levels alone is the key to the onset of sex change in honeycomb grouper, and that increasing testosterone (T) and 11KT levels following gonadal transformation could be stimulatory to male germ-cell proliferation and differentiation in the ovary.…”
Section: Introductionmentioning
confidence: 99%
“…Although abundance of red grouper has changed substantially over time, the sex ratio of the population has not changed greatly since 1975 (Coleman et al 1996). Peak spawning occurs in late spring, during March and May in the eastern Gulf of Mexico, but spawning may occur from January through June in the Gulf of Mexico and Caribbean Sea (Tables 9.12 and 9.13) (Johnson et al 1998). Red grouper are indeterminate batch spawners (Johnson et al 1998;Collins et al 2002).…”
Section: Key Life-history Processes and Ecologymentioning
confidence: 99%
“…Peak spawning occurs in late spring, during March and May in the eastern Gulf of Mexico, but spawning may occur from January through June in the Gulf of Mexico and Caribbean Sea (Tables 9.12 and 9.13) (Johnson et al 1998). Red grouper are indeterminate batch spawners (Johnson et al 1998;Collins et al 2002). Fecundity is related to size and ranges from 312,000 to 5,735,700 eggs.…”
Section: Key Life-history Processes and Ecologymentioning
confidence: 99%